Gamification at Universiti Malaysia Sabah: A Case Study of Enhancing English among Undergraduate Students - Lay Yoon Fah; Chang Siew Lee; Hamdan Adnan; Fong Soon Fook (2016)
In general, the term gamification is defined as the use of game facets in nongame contexts. This study aims at investigating undergraduate students’ perception on gamification as an alternative platform to facilitate their language learning processes as well as their acceptance of gamification according to gender. The psychometric properties of a questionnaire on the acceptance of gamification (PLE) particularly in terms of its validity and reliability were also examined in this study. Confirmatory factor analysis (CFA) was performed to test the reliability and validity of the measurement model by looking at the results of composite reliability, average variance extracted, and standardized loadings of the construct measures. Goodnessof- fit indices of the measurement model were also examined. The results of the study have shown that users of PLE were positive towards its usefulness in assisting their language learning and enhancing their performance, and confident of its ease of use. In general, the users have positive attitudes towards using PLE in language learning and they showed positive intention in using gamification in their future language learning. It is believed that this study would not only provide a good understanding of the undergraduate students’ acceptance of gamification in learning, but also shed light to the understanding of the future game use of these students. Therefore, it is recommended that gamification (PLE for instance) could be applied at the tertiary level in order to gamify educational contexts as one of the methods to make learning more interesting, motivational, and less conventional; and to promote autonomy and that learning does not remain within the boundaries of the classroom.